Clinical audit on treatment of mucosal and multiple cutaneous leishmaniasis lesions with pentavalent systemic antimony - Dilnawaz, Mansoor; Hussain, Khadim; Malik, Nasir Javed; Khan, Liaquat Mahmood; Mazhar, Hina; Soomro, Amanat Ali (Journal of Pakistan Association of Dermatologists, 2016)
Background Cutaneous leishmaniasis is a parasitic disease spread by the female sandfly occurring throughout the Americas from Texas to Argentina, and in the Old World, particularly the Middle East and North Africa. The condition is diagnosed every year in travelers, immigrants, and military personnel. The treatment mainstay is pentavalent antimony (e.g., sodium stibogluconate). Not all patients require treatment; many lesions heal spontaneously. The treatment is usually indicated in mucosal, mucocutaneous and multiple active cutaneous lesions. Methods 30 patients of cutaneous leishmaniasis were included from the dermatology ward. The method of data collection was retrospective. The basis of proposal was local guidelines. The audit type was process. The standard set was â€œ100% patients with mucosal and multiple cutaneous leishmaniasis lesions should be treated with pentavalent systemic antimonialsâ€. Results The result showed 100% compliance with our local guidelines in the analyzed cases.